Pelatihan Pembuatan Hand Sanitizer Cair dari Ekstrak Kulit Jeruk Nipis di Kawasan Wisata Desa Burai - Poedji Loekitowati Hariani; Fatma Fatma; Muhammad Said; Risfidian Mohadi; Salni Salni (Universitas Mataram, 2022)
Burai village is located in Tanjung Batu sub-district, Ogan Ilir district. Burai Village is a tourism mainstay village in Ogan Ilir district. This village is known as the colorful village. As an ecotourism destination, water tourism and fishing programs have been developed, as well as environmentally friendly fish farming through organic feed. Other tourism potentials, such as the existence of traditional Bari houses that are more than 200 years old, and songket crafts. As patients with the COVID-19 virus have decreased, the number of tourists visiting Burai village has also increased. Health protocols are still needed, one of which is the use of hand sanitizer. This community service activity is to provide training on making liquid hand sanitizer from lime peel extract with the target audience being the Burai village community, especially tourism service providers. Lime plant is one of the plants cultivated by the people of Burai village. Orange peel extract contains essential oils that function to inhibit the growth of bacteria. In addition, orange peel extract has a fresh aroma. Activities are carried out by giving lectures, training on making hand sanitizers and packaging them. With this activity, it is hoped that the community will be able to provide hand sanitizers for both their own needs and tourists. The results of the activity showed high community participation in activities, more than 75% of the target audience liked the aroma of lime peel extract hand sanitizer.